Corruption in the system of threats to economic security - E. I. Kuznetsova; E. V. Borisova (Путеводитель предпринимателя, 2020)
In modern conditions the corruption has all the necessary features for the recognition of its potential threat to state security, since corruption affects the General interests of the society. The authors consider the problem of corruption as a threat to national security and tak into account three vectors of destructive influence of corruption on the economy, law and the state.